KARAKTERISTIK DAN FAKTOR PERKAWINAN ANTARETNIS MINANG DAN JAWA DI KECAMATAN PAUH DUO KABUPATEN SOLOK SELATAN - Ahmad, Fadillah; Mariya, Sri (JURNAL BUANA, 2024)
The aims of this study: 1) To determine the sociodemographic characteristics of the Minang and Javanese interethnic couples in Pauh Duo District. 2) Analyzing the factors that influence inter-ethnic marriage. This type of research is descriptive with quantitative and qualitative approaches. The population in this study were all Minang and Javanese inter-ethnic couples. The sample was randomly selected as many as 100 respondents consisting of inter-ethnic married respondents and 50 inter-ethnic married respondents each. Samples were taken randomly in 5 nagari in Pauh Duo District. The data analysis technique used descriptive statistics and thematic analysis. The results showed: 1) Minang-Javanese couples were on average higher in terms of median age, age at marriage, and family members. Meanwhile, Javanese-Minang couples have higher levels of education, income, and first marriage. The number of inter-ethnic marriages increases 2-3 times every decade. 2) Of all inter-ethnic marriages, 33% are influenced by environmental factors, 32% educational factors, 24% economic factors, and 10% socio-cultural factors.